The Influence of the Kaliber TM Multimodal Program on Students’ Literacy at SDN 32 Ampenan - Siti Maulidiya Nabila; Rizka Aluna; Ulya Sulistina; Lalu Sumardi; Katrin Kohl (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
This study aims to examine the effect of the Kaliber TM Multimodal Program (Kamis Aksi Literasi based on Multimodal Texts) on the literacy of Grade V students at SDN 32 Ampenan. The study uses a quantitative method with an ex post facto approach, involving 40 students as the sample through a saturated sampling technique. The research instruments consist of a literacy questionnaire and observation sheets developed based on upper-grade elementary literacy indicators from the Ministry of Education, Culture, Research, and Technology, which include reading, writing, listening, and literacy habits. The results show that students’ literacy reached an average score of 78.5 (high category), with reading = 80.2, writing = 76.8, listening = 77.4, and literacy habits = 79.6. The simple linear regression test produced the equation Y = 52.3 + 0.46X, and the determination coefficient R² = 0.42, indicating that the program contributes 42% to literacy improvement. The t-test results (t = 4.92, t-table = 2.02) show a significant influence between the implementation of the program and students’ literacy. Therefore, the Kaliber TM Multimodal Program is proven effective in improving literacy skills of students at SDN 32 Ampenan and is suitable to be used as a model for strengthening literacy in elementary schools in the 21st century.